Analyzing Superiority of Tail Drop over Random Early Discard by evaluating throughput using varying queue length in 802.11 - Attiuttama; Sindhuben babulal, Kanojia (International Journal of Computer Sciences and Engineering, 2025)
Wireless network is used because of cost effectiveness in network deployment, and its applicability to environment where wiring is not possible wireless is preferable solution compared to wired networks. Congestion is a problem that happens due to surpass in an aggregate demand as compare to the accessible ability of the resources. It has a greater impact on both the wired and wireless network. Ns-2 is used in simulating system models, the loss in the channel can be easily distinguished from the trace file. Even though RED sometimes has better performance than Tail Drop and vice versa, we cannot say that RED has the dominance, because the total number of nodes in a real wireless network changes every moment. The average queue or buffer size of the RED is smaller than the average queue length of Tail drop.